2023
DOI: 10.5114/jhi.2023.129174
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nutritional status and eating habits of Polish women during the menopause transition – a pilot study

Julia Ponichter,
Paula Gosa,
Wojciech Giermaziak
et al.

Abstract: Introduction:The menopause is a natural biological process in a woman's life when the hormonal activity of the ovaries ceases. It has an impact on the woman's further life. In this study we analysed nutritional status and nutrition of women during the menopause transition. Material and methods:The study was carried out in 2018 using an online questionnaire survey. Data were obtained from 90 women from Poland aged between 40 and 55 years. The subjects were selected using the snowball method. The questionnaire i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Thus, early nutritional instruction is required, because a woman's bad eating habits may continue into the menopausal stage (34). This result is consistent with that of a previous study that found that the intake of fruits and vegetables was low among the participants (9,32,34,36,38,40). Conversely, another study reported the lowest intake for proteins, carbohydrates, fats, calcium, magnesium, phosphorus and iron among its participants (33).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Thus, early nutritional instruction is required, because a woman's bad eating habits may continue into the menopausal stage (34). This result is consistent with that of a previous study that found that the intake of fruits and vegetables was low among the participants (9,32,34,36,38,40). Conversely, another study reported the lowest intake for proteins, carbohydrates, fats, calcium, magnesium, phosphorus and iron among its participants (33).…”
Section: Discussionsupporting
confidence: 89%
“…A healthy diet consists of food with fiber, water, vitamins, minerals, proteins, carbohydrates, and fats (29). A healthy diet can reduce the risk of diseases and enhance quality of life (34). Moreover, adequate nutritional fulfillment can considerably reduce the negative consequences of menopause (29).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations